British Neurotoxin Network recommendations for managing cervical dystonia in patients with a poor response to botulinum toxin. Issue 4 (14th March 2016) - Marion, Marie-Helene; Humberstone, Miles; Grunewald, Richard; Wimalaratna, Sunil
Abstract : Botulinum toxin (BoNT) injections are an effective treatment for cervical dystonia. Approximately 20% of patients eventually stop BoNT treatment, mostly because of treatment failure. These recommendations review the different therapeutic interventions for optimising the treatment in secondary poor responder patients. Immunoresistance has become less common over the years, but the diagnosis has to be addressed with a frontalis test or an Extensor Digitorum Brevis test. In case of immunoresistance to BoNT-A, we discuss the place the different therapeutic options (BoNT-A holidays, BoNT-B injections, alternative BoNT-A injections, deep brain stimulation). When poor responders are not immunoresistant, they benefit from reviewing (1) injections technique with electromyography or ultrasound guidance, (2) muscles selection and (3) dose of BoNT. In addition, in both scenarios, a holistic approach including drug treatment, retraining and psychological support is valuable in the management of these complex and severe cervical dystonia.